1987
DOI: 10.1246/bcsj.60.444
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Cu2+ or Hg2+ Ion on Resins Prepared by Crosslinking Metal-Complexed Chitosans

Abstract: Crosslinking metal-complexed chitosans (metal ions=Cu(II), Cd(II), Zn(II), Ni(II), and Fe(III)) with (chloromethyl)oxirane yields resins having higher abilities to adsorb Cu2+ than a resin obtained from chitosan in the absence of metal ion. Resins from Cd(II)–chitosan complex can act as effective adsorbents for Hg2+; their Langmuir’s adsorption parameters depend on the quantity of (chloromethyl)oxirane used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
34
0
2

Year Published

1992
1992
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(37 citation statements)
references
References 7 publications
1
34
0
2
Order By: Relevance
“…In recent years, from the view point of environmental safety, much attention has been paid to the collection and separation of metal ions on various kinds of biomass, such as alginic acid, cellulose, chitin, and chitosan. [1][2][3][4] Chitosan is a glucosamine biopolymer, obtained by deacetylating chitin, which is one of the most abundant biomass. Chitosan, possessing amino groups and hydroxyl groups, is an excellent base material for analytical fields.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, from the view point of environmental safety, much attention has been paid to the collection and separation of metal ions on various kinds of biomass, such as alginic acid, cellulose, chitin, and chitosan. [1][2][3][4] Chitosan is a glucosamine biopolymer, obtained by deacetylating chitin, which is one of the most abundant biomass. Chitosan, possessing amino groups and hydroxyl groups, is an excellent base material for analytical fields.…”
Section: Introductionmentioning
confidence: 99%
“…Cross-linking can make chitosan hardly soluble in acidic media. Ohga et al reported that cross-linked chitosan, which was prepared by cross-linking with (chloromethyl)oxyrane after complexation of chitosan with metal ions, can act as effective adsorbents for Cu(II) and Hg(II), 9 and Inoue et al reported the adsorption behavior of 15 elements on cross-linked chitosan by a batchwise method.10,11 Koyama et al and Kurita et al also synthesized a cross-linked chitosan with glutaraldehyde, and examined the adsorption behavior of Cu. 12,13 Further, Rorrer et al examined adsorption isotherms of Cd(II) on porous chitosan beads crosslinked with glutaraldehyde at 25˚C and pH 6.5 over the concentration range 1 -1690 mg l -1 .…”
mentioning
confidence: 99%
“…Cross-linking can make chitosan hardly soluble in acidic media. Ohga et al reported that cross-linked chitosan, which was prepared by cross-linking with (chloromethyl)oxyrane after complexation of chitosan with metal ions, can act as effective adsorbents for Cu(II) and Hg(II), 9 and Inoue et al reported the adsorption behavior of 15 elements on cross-linked chitosan by a batchwise method.…”
mentioning
confidence: 99%
“…Such an experiment is a useful method to evaluate the imprinting effect, and has commonly been carried out in studies concerning metal-imprinted resin. [8][9][10][11][12] As can be seen in Table 1, the imprinted microspheres adsorbed the corresponding guest ions more effectively than did the unimprinted ones; the imprinting effect was thus clearly shown. The adsorption percentages at pH 5.6 were larger than those at pH 4.9, suggesting that the carboxyl ANALYTICAL SCIENCE'S OCTOBER 1992, VOL.…”
Section: Resultsmentioning
confidence: 99%